The effect of high oral loading dose of cholecalciferol in non-alcoholic fatty liver disease patients. A randomized placebo controlled trial - Mohamed, Amal Ahmed; Halim, Ahmed Abdel; Mohamed, Sahar; Mahmoud, Seham Mohamed; Bahgat Eldemiry, Eman Mohamed; Mohamed, Rasha Sobh; Shaheen, Mahmoud Maamoun; Naguib, Gina G.; Muharram, Nashwa M.; Khalil, Mona G.; Saed, Salma; Ibrahim, Randa; et al. (Frontiers in Pharmacology, 2023)
Background and Aim: Non-alcoholic fatty liver (NAFLD) is one of the most common progressive metabolic disorders worldwide. There are increasing scientific interests nowadays for the association between vitamin D status and NAFLD. Earlier studies have revealed that vitamin D deficiency is highly prevalent in NAFLD patients that contributes to poor outcomes. Hence, the present study aimed to assess the efficacy and safety of oral cholecalciferol on NAFLD patients. Subjects and Methods: This study was conducted on 140 patients that were randomized either to group 1 that received the standard conventional therapy in addition to placebo or group 2 that received the standard conventional therapy in addition to cholecalciferol during the 4 months study period. Results: At the end of the study group 2 revealed significant decrease (p<0.05) in the mean serum level of TG, LDL-C, TC, hsCRP as compared to their baseline results and group 1 results. Additionally, a significant improvement in the serum levels of ALT (p=0.001) was seen in group 2 at the end of the study when compared to group 1. Whereas group 1 didn’t show any change in these parameters when compared to group 2 and their baseline results. Conclusion: Cholecalciferol was shown to have beneficial effects on serum ALT levels, hsCRP levels and lipid profile of NAFLD patients.